Pengaruh Profitabilitas, Likuiditas, Dan Leverage Terhadap Nilai Perusahaan (Studi Kasus Pada Perusahaan Manufaktur Sub Sektor Food And Beverage Yang Terdaftar Di BEI Tahun 2018-2020) - Miswati Miswati; Ronny Malavia Mardani; Eris Dianawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study was conducted to test wether there is a partial effect between the variables Profitability, liquidity and leverage on company value. The researcher used secondary data with saturated samples and purposive sampling methods as determinats of the sample criteria. By obtaining a sample according to the criteria of 22 companies in the 2018-2020 period wiith data procssing using the SPSS aplication. The results show that profitability (Return on Assets) has a significant effect on firm value, liquidity (Current Ratio) does not negative affect firm value, leverage (Debt to Equity Ratio) has no significant effect on firm value. Keywords: Profitability, Liquidity, Leverage, Firm Value